Preparation of iron oxide nanoparticles stabilized with biomolecules: Experimental and mechanistic issues - Nicolás, Paula (2013)
Nanoparticles (NPs) with magnetic properties based on magnetite (Fe3O4, MAG) modified with oleic acid (OA), chitosan (CS) and bovine serum albumin (BSA) have been prepared. A versatile method of synthesis was employed, involving two steps: (i) co-precipitation of MAG; and (ii) nanoprecipitation of macromolecules on as-formed MAG NPs. Experimental variables have been explored to determine the set of conditions that ensure suitable properties of NPs in terms of their size, functionality and magnetic properties. It was found that the presence of OA in Fe+2/Fe+3 solutions yields MAG NPs with lower aggregation levels, while increasing initial amounts of OA may change the capability of NPs to disperse in aqueous or organic media by modifying the stabilization mechanism. Incorporation of CS was verified through Fourier transform IR spectroscopy. This biopolymer stabilizes NPs by electrostatic repulsions leading to stable ferrofluids and minimal fraction of recoverable solid NPs. BSA was successfully added to NP formulations, increasing their functionality and probably their biocompatibility. In this case too stable ferrofluids were obtained, where BSA acts as a polyelectrolyte. From the proposed methodology it is possible to achieve a wide range of NPs magnetically active intended for several applications. The required properties may be obtained by varying experimental conditions.